Estimation of Orangutan Population in Sibongkaras Pakpak Bharat Village Forest Area - Juhardi Sembiring; Taufiq Siddiq Azvi (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract : Orangutan is classified as an endangered species. Forest clearance for a variety of purposes and functions over the region led to the limited habitat for orangutans. Orangutans habitat is fragmented into several regions led to the survival of a population of a species depends on habitat conditions. Performing a nest survey is important to give a deeper understanding of the ecology and help determine the best protective management measures. We provide basic data of orangutan density and orangutan nesting characteristics in protected forest area Sibongkaras village. This study was conducted in April 2019 until June 2019 in protected forest area Sibongkaras village, Pakpak Bharat. Tracking begins with observed the presence of a nest based on a purposive sampling method. And data retrieval was done by line transect method. Data analyzed at Universitas Nahdlatul Ulama Sumatera Utara. Our result showed that the orangutan population density was 0.0072 individuals/km2 or 0.72 individuals/ha. The dominant position of the nest is in a position which is a position I nest close to the main stem of the tree with the nest number 13 (43.3%). Generally, the nest is found at an altitude of  >15 meters with a sum of 27 nests (90%).Abstrak : Orangutan diklasifikasikan sebagai spesies yang terancam punah. Penebangan hutan untuk berbagai tujuan dan fungsi di kawasan tersebut menyebabkan terbatasnya habitat orangutan. Habitat orangutan yang terfragmentasi menjadi beberapa wilayah menyebabkan kelangsungan hidup suatu populasi suatu spesies tergantung pada kondisi habitat. Melakukan survei sarang penting untuk memberikan pemahaman yang lebih dalam tentang ekologi dan membantu menentukan langkah-langkah manajemen perlindungan terbaik. Kami menyediakan data dasar kepadatan orangutan dan karakteristik sarang orangutan di kawasan hutan lindung Desa Sibongkaras. Penelitian ini dilakukan pada bulan April 2019 hingga Juni 2019 di kawasan hutan lindung Desa Sibongkaras, Pakpak Bharat. Pengamatan dimulai dengan mengamati keberadaan sarang berdasarkan metode purposive sampling. Dan pengambilan data dilakukan dengan metode transek garis. Data yang diperoleh di analisis di Universitas Nahdlatul Ulama Sumatera Utara. Hasil Penelitian kami menunjukkan kepadatan populasi orangutan di 0,0072 individuals/km2 atau 0,72 individu / ha. Posisi sarang yang dominan adalah pada posisi sarang yang berada di posisi paling dekat dengan batang utama, dengan jumlah sarang 13 (43,3%). Umumnya sarang ditemukan di ketinggian > 15 meter dengan jumlah 27 sarang (90%).